2011
DOI: 10.1007/s00198-010-1525-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum sclerostin levels positively correlate with lumbar spinal bone mineral density in postmenopausal women—the six-month effect of risedronate and teriparatide

Abstract: Sclerostin is expressed by osteocytes and inhibits bone formation by osteoblasts. In this study, serum sclerostin was positively correlated with either lumbar spinal bone mineral density or T-score. Furthermore, serum sclerostin was increased after 6 months treatment with risedronate, whereas remained unchanged after 6 months teriparatide treatment. Introduction The primary aim of this study was the evaluation of serum sclerostin levels in postmenopausal women and their association with bone mineral density (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
58
5
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 17 publications
18
58
5
3
Order By: Relevance
“…Thus, the possibility remains that 1,25(OH)2D3 links FGF23 to bone destruction and osteoporosis, which warrants investigation. Furthermore, sclerostin is a humoral factor that strongly inhibits bone formation (31) and elevated circulating levels of this factor are associated with the incidence of osteoporosis in postmenopausal women (32). Because sclerostin is also released from osteocytes (33), its net function may be indicated by circulating FGF23 levels, which may in turn be affected by osteocyte activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the possibility remains that 1,25(OH)2D3 links FGF23 to bone destruction and osteoporosis, which warrants investigation. Furthermore, sclerostin is a humoral factor that strongly inhibits bone formation (31) and elevated circulating levels of this factor are associated with the incidence of osteoporosis in postmenopausal women (32). Because sclerostin is also released from osteocytes (33), its net function may be indicated by circulating FGF23 levels, which may in turn be affected by osteocyte activity.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, given that Scl inhibits osteoblastic activity, a negative correlation would be expected. However, some studies have also found direct correlations between serum Scl and BMD (48,49) or BV/TV in healthy populations (50).…”
Section: Discussionmentioning
confidence: 99%
“…Para el análisis estadístico se utilizaron las técnicas de regresión lineal 13,28,29 y de regresión logística 1,4,18,20,21,23 con el uso del SPSS para Windows versión 16.…”
Section: Con El Eq-5dunclassified